DEVELOPING ENGLISH ASSESSMENT BY ACCOMODATING LOCAL CULTURE FOR GRADE SEVEN OF JUNIOR HIGH SCHOOL IN BULELENG SUB-DISTRICT TO SUPPORT THE IMPLEMENTATION OF CURRICULUM 2013 - ., I Wayan Heri Sumardika; ., Ni Komang Arie Suwastini, S.Pd,M.Hum.; ., Drs.Gede Batan,MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Peneliatian ini berbentuk penelitian pengembangan yang bertujuan untuk mengembangkan suatu produk. Adapun produk yang dikembangkan yaitu instrument penilaian pembelajaran Bahasa Inggris yang berbasis budaya lokal untuk kelas VII SMP semester ganjil di Kecamatan Buleleng. Produk ini diharapkan mampu menunjang pengimplementasian Kurikulum 2013. Model peneliatian dan pengembangan diadopsi dari model penelitian dan pengembembangan oleh Peffers et al. (2007) dalam Ellis dan Levy (2010) yang terdiri dari enam tahapan penelitian. Penelitian ini didasari oleh penelitian yang telah dilakukan oleh Dewi dan Batan (2015). Setting dari penelitian ini adalah 9 SMP di Kecamatan Buleleng. Nilai-nilai budaya Bali dan nilai-nilai pendidikan karakter diintegrasikan dalam instrumen penilaian. Instrumen tersebut meliputi penilaian terhadap sikap, pengetahuan, dan keterampilan siswa. Data yang diperoleh dalam peneliatian diolah secara kualitatif dan kuantitatif. Kualitas dari instrument penialaian telah diujikan melalui panel ahli. Terdapat 3 aspek telah diuji oleh ahli, meliputi aspek validitas, reliabilitas, dan kepraktisan. Berdasarkan nilai yang diberikan oleh kedua ahli, kualitas dari instrument penilaian tergolong sempurna. Nilai oleh ahli pertama adalah 642 dan ahli kedua adalah 807. Reliabilitas data diukur menggunakan koefisien Alpha Cronbach’s. Hasilnya, reliabilitas produk adalah 0.997 dan dapat digolongkan sebagai sempurna. Produk instrumen penilaian yang berbasis budaya ini memiliki kualitas dan reliabilitas sempurna. Kata Kunci : Instrumen Penilaian, Penilaian Bahasa Inggris, Budaya Bali, dan Kurikulum 2013 This research was aimed at designing and developing English assessment by accommodating local culture for the first semester of grade seven of junior high schools in Buleleng sub-district to support the implementation of curriculum 2013. This research was designed as a research and development by following RnD model proposed by Peffers et.al (2007) in Ellis and Levy (2010) which consisted of six steps. The data of need analysis were obtained from the result of Dewi and Batan (2015) research and analysis the syllabus. Settings of this research were nine junior high schools in Buleleng sub-district. Balinese cultural values and character values in the assessment were integrated through the assessment instrument. The assessment covered affective domain, cognitive domain, and psychomotor domain. The data were analyzed both qualitatively and quantitatively. The quality of the assessment instrument was assessed through expert judgment to determine its worthiness. Three aspects in the assessment were assessed through the expert judgment forms, namely validity, reliability, and the practical aspect. Based on the scores given by two experts, the quality of the assessment instrument was categorized as excellent quality since the score given by expert I was 642 and expert II was 807. The reliability of the data was measured by using Alpha Cronbach’s coefficient. The result showed that α Cronbach’s coefficient was 0.997 and it was categorized as excellent. In short, the developed culture-based English assessment has excellent quality and the data were reliable. keyword : Balinese culture-based English assessment, English assessment for Junior High School, RnD Assessment